Eta y el Cine. Las fuentes de información de los profesionales del cine - Malalaña Ureña, Antonio; Fernández González, Gonzalo (Revista General de Información y Documentación, 2007)
In 1976, Iñaki Núñez started shooting his first film about ETA. Since then, he has made nearly forty films, both fiction and documentaries. With a few exceptions, for both kinds of film, the use of sources of information has been fundamental in order to write the script and useful in order to fix the setting. The objective is to identify the documentary resources used in each of the films selected, systemise them, find out where they come from, and identify how each of them has been used.